Komunikasi Kota Ruang Publik Taman sebagai Pembentuk Citra Kota Hijau - Mariana Rista Ananda Siregar (Institut Pertanian Bogor, 2019)
Building an image of an area now has become the concern of many local governments in shaping the image of the city or region. Place branding is part of the study of city branding which is part of an effort to plan cities in building differentiation of images and strengthening brands. Bogor City as one of the supporting cities of capital city has a lot of potential natural resources, human resources and environmental resources that support in building the city image as a Green City. This study aims to describe the efforts of the Bogor City government in building the city image as a Green City. This paper is based on several research authors with a sequential method approach using data collected through qualitative and quantitative methods. Instead of communicating with the city marketing using media publications, the City of Bogor Government prefers to build its city image in the public's mind through a landscape strategy approach in carrying out the city's primary communication. The landscape strategy carried out by the Bogor City government in building its city image is carried out by building city parks, structuring and expanding green open spaces as a city attraction that is also seen and felt by its citizens.